O SUICÍDIO NOS INQUÉRITOS POLICIAIS DE INÁCIO MARTINS – PR (1974 - 2014) - BORGES, Augusto (2017)
The aims of this research is to analyse how people interpret, speak or relate to death (more specifically death of suicide) in the city of Inácio Martins. Taking a survey in the city's police files we were able to catalog between 1974 and 2014, 21 suicides occurred in said ville. Such cases it carried out by means of firearms; white guns and hangings. Because it is an little city, where everyone knows each other, there is a feeling of belonging among the citizens in this city. Therefore, from the moment a member of this group decides to abbreviate its existence, it generates a strangeness in the population, followed by sensations that arouse curiosity, compassion, anger and even fear of the contagion of death. The spaces where the voluntary deaths occur take on a mystical character, cursed. Those who leave for autocide leave in this world a trail of feelings and uncertainties. The biggest of them translates into a painful one: "Why? "